PENGARUH KUALITAS LAYANAN DAN PENGALAMAN PENGGUNA TERHADAP MINAT PENGGUNAAN ULANG DENGAN KEPUASAN PENGGUNA SEBAGAI VARIABEL INTERVENING PADA KONSUMEN GRAB BIKE DI KOTA SEMARANG (Studi pada Mahasiswa Universitas Diponegoro) - Parahita, Dyaksa Witsqa; Raharjo, Susilo Toto (Diponegoro Journal of Management, 2024)
ABSTRACT Research was only conducted on the influence of service quality and user experience on reuse intentions with user satisfaction as a intervening variable for Grab Bike consumers in Semarang City. This research aims to determine the influence of service quality and user experience on reuse intentions with user satisfaction as a mediating variable among Grab Bike consumers in Semarang City. The population in this study were Undip students who used Grab bikes in the city of Semarang. This research used a positive sampling technique, where samples were taken based on criteria, obtaining a total of 130 respondents. Data collection uses a questionnaire by distributing a list of questions to respondents to obtain information. The analysis technique in this research uses Structural Equation Modeling (SEM) with AMOSS Software 25. The results of the research are: service quality has a positive and significant influence on intention to reuse, service quality has a positive and significant influence on user satisfaction, user experience has a positive and significant influence on intention to reuse, user experience has a positive and significant influence on service user satisfaction , and user satisfaction have a positive and significant influence on reuse intentions.